2005
DOI: 10.1111/j.1523-1755.2005.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of subclinical and clinical hypothyroidism in persons with chronic kidney disease

Abstract: Among a nationally representative sample of adults, reduced glomerular filtration rate was associated with a higher prevalence of hypothyroidism, with many subclinical cases. Future studies are needed to determine the potential adverse effects of subclinical and clinical hypothyroidism in persons with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
263
6
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(302 citation statements)
references
References 22 publications
22
263
6
11
Order By: Relevance
“…Interestingly, CKD was found to be associated with a greater prevalence of clinical and subclinical primary hypothyroidism among participants of the Third National Health and Nutrition Examination Survey (4). Recently, we extended these findings in a large non-US cohort of outpatients by showing that the prevalence of subclinical hypothyroidism increases as estimated glomerular filtration rate (eGFR) decreases (5).…”
Section: Introductionmentioning
confidence: 50%
“…Interestingly, CKD was found to be associated with a greater prevalence of clinical and subclinical primary hypothyroidism among participants of the Third National Health and Nutrition Examination Survey (4). Recently, we extended these findings in a large non-US cohort of outpatients by showing that the prevalence of subclinical hypothyroidism increases as estimated glomerular filtration rate (eGFR) decreases (5).…”
Section: Introductionmentioning
confidence: 50%
“…In humans, subclinical hypothyroidism is associated with cardiac dysfunction, atherosclerosis, and hypercholesterolemia 36, 37, 44. Interestingly, there also appears to be an increased prevalence of subclinical hypothyroidism in people with CKD 45. A recent study of subclinical hypothyroidism and CKD found that human patients receiving L‐T 4 supplementation had slower declines in GFR and were less likely to develop end‐stage CKD than those receiving a placebo 46.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the third national survey in the United States revealed, that among patients with chronic kidney disease, the prevalence of hypothyroidism increases with lower levels of glomerulus filtration rate (GFR), in subjects with GFR <30 ml/min/1.73m 2 the prevalence was 23.1% [11]. In another cross-sectional analysis in Italy, the prevalence of subclinical hypothyroidism was found to be 17.9% in persons with GFR <60 ml/min/1.73m 2 [12].…”
Section: Discussionmentioning
confidence: 99%